The Interpolation Evolution Method for damage localization in structures under seismic excitation. (29th May 2018) - Iacovino, C.; Ditommaso, R.; Ponzo, F.C.; Limongelli, M.P.
Summary: In the aftermath of an earthquake, data acquired by a monitoring system can be used to identify possible damage that occurred in the structure by using algorithms to estimate proper damage features. In this paper, a new method is proposed for damage localization in beam‐like structures under seismic excitation. The proposed algorithm, named the Interpolation Evolution Method (IEM), is based on the combination of two existing methods: the Interpolation Method and the Curvature Evolution Method. Only responses recorded in story accelerations are required to estimate the damage feature with the combined IEM approach. This method does not require a priori knowledge of a "signature" of the structure because it exploits responses recorded during a single strong motion event. Herein, the IEM is applied to case studies of 2 reinforced concrete frames excited by several different ground motions, simulated using nonlinear finite element models and recorded during experimental tests carried out on a shaking table at the University of California, San Diego (USA) and at the University of Basilicata (Italy).